Can Government Purchases Stimulate the Economy? - Ramey, Valerie A (Journal of Economic Literature, 2011)
This essay briefly reviews the state of knowledge about the government spending multiplier. Drawing on theoretical work, aggregate empirical estimates from the United States, as well as cross-locality estimates, I assess the likely range of multiplier values for the experiment most relevant to the stimulus package debate: a temporary, deficit-financed increase in government purchases. I conclude that the multiplier for this type of spending is probably between 0.8 and 1.5. (JEL E23, E62, H50)